PERANCANGAN PEMBUATAN PERMEN KAPAS OTOMATIS BERBASIS ARDUINO UNO - Nurwijayanti Kusumaningrum; Fitriah Fitriah (TESLA: Jurnal Teknik Elektro, 2020)
Cotton candy is one of Indonesia's traditional foods which was quite popular in its time. Cotton candy is made from sugar that is given food coloring, cotton candy is made using a special tool that rotates and produces refined sugar fibers. Most cotton candy consists of air cotton candy feels sweet and sticky. Even though it looks like wool yarn ... The design of this cotton candy maker uses an arduino uno microcontroller, equipped with a temperature sensor, 3 push buttons and a heating stove as a heating container for the sugar container design of this tool. All Arduino Uno microcontroller working systems have been programmed using the C program language on the Arduino Uno microcontroller. Using a dose of 1/2 spoonful sugar, the average initial temperature (54.5 ° C) and the average final temperature (64.8 ° C) were obtained. Measuring one (1) spoonful of sugar, the initial heating temperature with an average (68.8oC) average final temperature (74.2oC). The dose of sugar 1 1/2 spoon, the initial temperature of the heater with an average (70.4 ° C) the average temperature of the final heater (77.4). This tool takes time to heat the heating stove in approximately 2 minutes to reach ambient temperature (54oC). Testing to find out the exact time of each dose of sugar. as in the dose of half a sugar (1/2) a spoon an average of about 120 seconds is obtained, a dose of sugar (one) spoon is obtained an average time of about 150 seconds and in a sugar one and a half (1½) spoon an average time is obtained about 180 seconds. ABSTRAK:Permen kapas adalah salah satu makanan tradisional khas Indonesia yang cukup populer pada masanya. Permen kapas dibuat dari gula yang diberi pewarna makanan, permen kapas dibuat menggunakan sebuah alat khusus yang berputar  dan menghasilkan serat – serat gula yang halus. Sebagian besar permen kapas terdiri dari udara permen kapas terasa manis dan lengket. Meskipun terlihat seperti benang wol..Perancangan pembuat permen kapas ini menggunakan mikrokontroler arduino uno, dilengkapi sensor suhu, 3 buah push button  dan kompor pemanas sebagai pemanas wadah penampung gula perancangan alat ini. Semua sistem kerja mikrokontroller arduino uno  sudah diprogram menggunakan bahasa program C  pada mikrokontroler Arduino Uno.Menggunakan takaran gula 1/2 sendok, didapatkan suhu awal rata-rata (54,5oC) dan suhu akhir rata-rata (64,8oC).  Takaran gula satu (1) sendok, suhu awal pemanas dengan rata-rata (68,8oC) suhu akhir rata-rata (74,2oC). Takaran gula 1 1/2 sendok, suhu awal pemanas dengan rata-rata (70,4oC) suhu akhir pemanas rata-rata (77,4). Alat ini membutuhkan waktu untuk memanaskan kompor pemanas dalam waktu kurang lebih 2 menit  untuk mencapai suhu sekitar (54oC). Pengujian untuk mengetahui waktu yang tepat dari setiap takaran gula. seperti pada takaran gula  setengah (1/2) sendok diperoleh rata-rata waktu sekitar120 detik, takaran gula  satu (1) sendok diperoleh rata-rata waktu sekitar150 detik dan pada takarang gula satu setengah (1 ½) sendok diperoleh rata-rata waktusekitar 180 detik.